Does Entrepreneurship Education and Technopreneurship Literacy among Students Contribute to Entrepreneurial Interest through Self Efficacy? - Nasruddin Nasruddin; Gamar Al Haddar; Amraeni Amraeni; Mukhtar Tahir; Murthada Murthada (Universitas Negeri Makassar, 2023)
This study aims to determine whether entrepreneurship education and technopreneurship literacy among students contribute to entrepreneurial interest through self-efficacy in Vocational High School students. This research is categorized as quantitative research with a population of 500 Vocational High School students and a sample of 100 students. Data collection was done with documentation and questionnaire techniques. The analysis technique used is path analysis using SPSS software. Research shows that both directly and indirectly entrepreneurship education and technopreneurship literacy contribute to positive and significant interest in entrepreneurship through self-efficacy in vocational high school students. Based on the results of this study, entrepreneurship education and technopreneurship literacy are very important to start teaching and given to students in Vocational High Schools, not only in one particular department but need to be taught in all departments, because with entrepreneurship education and technopreneurship literacy can increase self-efficacy and and ultimately can contribute to entrepreneurial interest in students.